AN AUTONOMOUS BRAKING CONTROL SYSTEM FOR A 2017 YAMAHA GRIZZLY 700 - Greg WHEATLEY; Robiul Islam RUBEL (Scientific Journal of Silesian University of Technology. Series Transport)
Weed control is an important issue for environmental protection all around the world. Traditional hand weed control is laborious whereas chemical control is costly and a threat to the atmosphere. A chemical patch weed control system is an optimized system but lacks cheap technical equipment. This research outlines a design process and test of a braking system that can be applied during the designing of an autonomous braking system for a 2017 Yamaha Grizzly 700. The system is intended to be used as an autonomous weed chemical spraying. A bolt-on approach that did not require any manipulation of the stock, an internal braking system was followed to reduce the complexity and installation time of multiple systems. Three different types of autonomous braking system solutions were initially investigated, with the linear actuator solution being decided on through the assistance of a weighted decision matrix. The system was designed around a 30 kg hand force; however, a spare actuator of approximately 20 kg of force was repurposed and used instead. Finite element analysis concluded that all major components within the proposed system were suitable for a lifetime of at least 1,000,000 cycles with a mild steel yield stress failure criterion of 370 MPa. A stationary test for the system was conducted to determine the success of the system, which pushed the brake lever approximately 25% of its disengaged handlebar to lever length. The resulting system met the requirements of the expectation and could be used to apply the ATV’s brakes autonomously while retracting the gear interlocking mechanism enough to change gears.